From Character Strengths to Children’s Well-Being: Development and Validation of the Character Strengths Inventory for Elementary School Children - Shoshani, Anat; Shwartz, Lior (Frontiers in Psychology, 2018)
Although research on character strengths has flourished in recent years, the paucity of suitable quantitative instruments for the assessment of children's character strengths limits the study of character development in childhood. The Character Strengths Inventory for Children (CSI-C) is a new self-report character inventory for children that was designed for easy administration directly to elementary school‐aged children. The CSI-C provides an evaluation of 24 character strengths defined in Peterson and Seligman's Values in Action Classification of Strengths. Data from two samples of 2,061 Israeli children aged 7 to 12 support the constructs of the instrument. Principal component analysis and confirmatory factor analysis of the 96 CSI-C items revealed preliminary evidence for a hierarchical structure with 24 lower factors nested within four higher-order latent factors: interpersonal, transcendence, intellectual, and temperance strengths. Children's interpersonal and temperance strengths were negatively associated with mental health difficulties, and their temperance and transcendence strengths were positively associated with subjective well-being. The intellectual and temperance strengths were correlated with children's school functioning and grit. The potential uses of the CSI-C in research and practice are discussed.